2017
DOI: 10.1051/epjconf/201714003063
|View full text |Cite
|
Sign up to set email alerts
|

A microscopic theory for discontinuous shear thickening of frictional granular materials

Abstract: Abstract. We extend a recent theory for the rheology of frictionless granular materials [1] to the case of frictional disks in two dimensions. Employing a frictional contact model for molecular dynamics simulations, we derive difference equations of the shear stress, the granular temperature, and the spin temperature from the generalized Green-Kubo formula, where all the terms are given by microscopic expressions. The numerical solutions of the difference equations not only describe the flow curve, but also re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The difficulty including the mutual friction in terms of statistical mechanics is to have the contributions from the coupled stress and the spin temperature in addition to the shear stress, the normal stress difference and the pressure. A recent paper has already partially reproduced a hysteresis in the flow curve, which is one of the characteristics of the DST by choosing the shear stress, the temperature (the pressure) and the spin temperature [58].…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty including the mutual friction in terms of statistical mechanics is to have the contributions from the coupled stress and the spin temperature in addition to the shear stress, the normal stress difference and the pressure. A recent paper has already partially reproduced a hysteresis in the flow curve, which is one of the characteristics of the DST by choosing the shear stress, the temperature (the pressure) and the spin temperature [58].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent works have sought to explain DST as a transition from a state where hydrodynamic lubrication forces prevent particles from prolonged contact, to a state where such lubrication forces are overcome, particle contacts increase, and elastic Coulomb frictional forces at those contacts become important [49][50][51][52]. Other works [15,17,19,20,51,[53][54][55] have described DST as a precursor of the discontinuous jump in stress associated with the shear-driven jamming of frictional particles [15,16]. While both DST and shear banding have been associated with discontinuous transitions, it remains unclear if there is a direct connection between these two phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…This study will be reported elsewhere [40] (see also Ref. [41]). We should note that contact states between grains are important to describe typical DSTs in dense suspensions.…”
Section: Discussionmentioning
confidence: 83%